2017
DOI: 10.1002/hep.29303
|View full text |Cite
|
Sign up to set email alerts
|

Significance of oliguria in critically ill patients with chronic liver disease

Abstract: CLD patients have a high incidence of AKI. Compared with creatinine criteria alone, incorporating UO into the diagnostic criteria increased the measured incidence of AKI. Stage 2-3 AKI-UO has a high negative impact on hospital mortality. (Hepatology 2017;66:1592-1600).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 22 publications
1
60
1
3
Order By: Relevance
“…However, the urine output was removed in the new consensus definition of AKI, which raised some arguments about the use of urine output in patients with cirrhosis. A recent study from the University of Pittsburgh reported that patients with oliguria had a nearly 3-fold increased rate of hospital mortality compared with patients without AKI in critically ill patients with chronic liver disease [22]. In our study, the predictive ability of ICA criteria was non-inferior to that of KDIGO, in spite of removal of urine output.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the urine output was removed in the new consensus definition of AKI, which raised some arguments about the use of urine output in patients with cirrhosis. A recent study from the University of Pittsburgh reported that patients with oliguria had a nearly 3-fold increased rate of hospital mortality compared with patients without AKI in critically ill patients with chronic liver disease [22]. In our study, the predictive ability of ICA criteria was non-inferior to that of KDIGO, in spite of removal of urine output.…”
Section: Discussioncontrasting
confidence: 45%
“…7 More recently it was observed that adding the urine output (UO) diagnostic criteria of AKI to the assessment of critically ill patients with chronic liver disease, in the intensive care unit, improved the identification of patients with AKI, as well as of those with stage 2-3 AKI. 33 Additionally, patients identified based on UO criteria without sCr elevation had a significantly higher mortality. 33 In patients with cirrhosis, as in patients without cirrhosis, AKI can be due to prerenal, intrarenal or intrinsic (acute tubular necrosis, acute interstitial nephritis, acute glomerular and vasculitic renal diseases) and/or post-renal (acute obstructive nephropathy) causes.…”
Section: What Is New In the Definition And Classification Of Renal Dymentioning
confidence: 99%
“…33 Additionally, patients identified based on UO criteria without sCr elevation had a significantly higher mortality. 33 In patients with cirrhosis, as in patients without cirrhosis, AKI can be due to prerenal, intrarenal or intrinsic (acute tubular necrosis, acute interstitial nephritis, acute glomerular and vasculitic renal diseases) and/or post-renal (acute obstructive nephropathy) causes. Additionally, HRS-1 should be included in the differential diagnosis.…”
Section: What Is New In the Definition And Classification Of Renal Dymentioning
confidence: 99%
“…(4)(5)(6)(7) This is particularly true in those with AKI who then progress to persistent kidney injury, where the 30-day mortality rate is nearly 10-fold higher. (4,5,8) These findings highlight the importance of identifying the predictors of AKI as it is a potentially preventable and reversible condition. (9)(10)(11) To date, most studies evaluating AKI in patients with cirrhosis have included only those who are hospitalized.…”
mentioning
confidence: 96%
“…Regardless of the cause, the development of acute kidney injury (AKI) has a profound impact on survival . This is particularly true in those with AKI who then progress to persistent kidney injury, where the 30‐day mortality rate is nearly 10‐fold higher . These findings highlight the importance of identifying the predictors of AKI as it is a potentially preventable and reversible condition …”
mentioning
confidence: 99%